Development of mesoporous carbon nanocomposites film from synthetic precursor and natural cellulose incorporated with Mn₂O₃ for supercapacitor application - Sarif @ Mohd Ali, Mahanim (2020)
A good matching between the electrode material, pore size suitable for diffusion of electrolyte ions and the dimensions of ionic species is necessary for an optimal performance of electrode materials. By developing a cost-effective mesoporous carbon (MPC) electrode material with highly developed surface area and high electric conductivity may address the issues to enhance the capacitive performance of the material as well as power density, energy density and its cycle life. Thus, this study aims at developing MPC film from Resorcinol(R) /Formaldehyde(F)/F127 and modifying the carbon precursor using natural cellulose of carboxymethyl cellulose (CMC) before incorporated with manganese oxide (Mn2O3). That is purposedly to enhance the capacitance attributed from electric double layer (EDLC) properties in MPC film as well as the pseudocapacitive properties from faradaic redox reactions of Mn2O3. All samples were synthesised by using a spin coating self-assembly soft templating method and incipient wetness impregnation followed by calcination. The experimental conditions such as carbonisation temperature, molar ratio, stirring time, concentrations and calcination temperature and time were manipulated to enhance the capacitive performance of the electrode materials. X-ray diffraction (XRD), Fourier transform infrared (FTIR), Raman spectroscopy, X-ray photoelectron spectroscopy (XPS) and field emission scanning electron microscopy (FESEM) analysis was conducted to confirmed the structure and surface morphology of the samples. The electrochemical measurements e.g. cyclic voltammetry (CV) and galvanostatic charge/discharge (GCD) measurement was performed in 1 M potassium chloride (KCl) electrolyte solution in a three-electrode system assembly. From the results, it was revealed that the specific capacitance of Mn2O3/MPC composites film calcined at 300 °C showed 3.5 times higher with 53.59 mF cm-2 than optimised MPC film only 15.23 mF cm-2. These are in good agreement with the impressive results of a low internal resistance value recorded for Mn2O3/MPC, which could lead to the interpretation of higher specific capacitance compared to MPC as supported by the CV and GCD results. Mn2O3/MPC composite film displayed the highest energy and power density and shows fairly stable capacitance with sample could retain about 71% of its initial capacitance until reaching 1000 cycles. Then the research geared onwards by applying green raw material which is CMCs as a carbon source for the electrode materials. In this study, two types of CMC; bamboo CMC and agro-based CMC commercial were used before Mn2O3 incorporation. The enhancement in specific capacitance with 31.98 mF cm-2 for Mn2O3/CMCPCbam was observed to be 3.3 times higher compared to pure carbon samples. Mn2O3/CMCPCbam and Mn2O3/CMCPCcom show a relatively stable capacitance of around 65.6% and 68.5% of the initial capacitance after 1000 charge-discharge cycles and showing highest energy and power density. The incorporation of pseudocapacitance metal oxides with EDLC carbon films is therefore an effective way to increase electrochemical performance in terms of specific capacitance, power density and energy density characteristics of carbon materials. The presence of Mn2O3 was strongly proved by the XRD, XPS and FTIR analysis while FESEM-EDX and HRTEM confirmed their existence in the structure. This strategy highlights well-organised mesoporous carbon films from synthetic and natural cellulose precursor with superior electrochemical performance as the promising materials for advanced supercapacitor applications.